Pink Floyd the wall [videorecording (DVD)] : movie - Geldof, Bob, 1951-; Hargreaves, Christine, 1939-1984; Laurenson, James, 1940- (Sony BMG Music Entertainment, 2005)
"The story of the wall" is told simply with the music of Pink Floyd, images and natural effects. There is no conventional dialogue to progress the narrative. The story is about Pink, a rock and roll performer, who sits locked in a hotel room, somewhere in Los Angeles. Too many shows, too much dope, too much applause, a burned out case. On the TV, an all too familiar war film flickers on the screen. We shuffle time and place, reality and nightmare as we venture into Pink's painful memories, each one a "brick" in the wall he has gradually built around his feelings.